Learner Perspective of L1 Use in L2 Collaborative Writing: An Emic View - Mohanraj, Sathuvalli; Chimirala, Uma Maheshwari (ELT Worldwide: Journal of English Language Teaching, 2014)
Studies investigating the use of L1 in the L2 classroom space have done so from three viewpoints: the teacher’s use of L1, the learner’s perspective about the teacher’s use of L1 and the learner’s use of L1 in L2 writing as the learners participate in think aloud protocols or in collaborative writing. All three perspectives present the etic view of the act of using the L1 and report mixed and sometimes contradictory findings of what learners’ feel about the role L1 can play in the L2 learning context. Rarely have studies explored the learner’s perspective of their own use of L1 after a collaborative writing activity. By and large the image that emerges from the learners’ perspective is that the L1 is useful but thatit could be a blockade and a hindrance in acquiring the L2. We ask if this view would still persist if the learners were to bank on their L1 capabilities rather than comment on their Teacher’s Bi/Multilingual capabilities. Therefore, we interviewed 24, class 8, beginner level dyad writers (12 pairs) in a Zillah Parishad High School after they had collaboratively created three texts together. Qualitative analysis of the dyad interviews suggests that the learner’s need to be ‘allowed’ to explore their language capabilities before they realize the pedagogic potentiality of the L1 and decide on whether L1 is useful or otherwise. Key words: L1 use in L2 collaborative writing; learner’s perspective; emic view